The palynological study of some Hypericum taxa and its systematic significance - Kursat, Murat; Baser, Birol; Ozbey, Fahrettin; Emre, Irfan (Natl Taiwan Univ Press, 2025)
To expose their characteristics and assess their systematic relevance, the palynomorphology of 30 taxa belonging to the Hypericum genus (21 species, four subspecies, and five varieties), of which five are endemic, were examined using light and scanning electron microscopy. The studied Hypericum taxa pollen grains were monads; isopolar or heteropolar; small to medium size; oblate-spheroidal, prolate-spheroidal, subprolate, spheroidal, and prolate in shape. It was shown that over 20% of the pollen observed (i.e., 13 taxa) was irregular (syncolp(or)ate, pantocolp(or)ate) in terms of aperture number and configuration. The remaining 17 taxa had only 3-colp(or)ate grains typical of the genus. The analyzed taxa were grouped into four categories based on exine sculpturing: microreticulate, microreticulate-perforate, reticulate, and reticulate-perforate. Moreover, four distinct taxonomic groupings were shown due to the UPGMA cluster analysis made to evaluate the morphological characteristics of the studied taxa's pollen. Additionally, due to a PCA ordination, pollen diameter, colpus length, and mesocolpia played significant roles in the ordination and confirmed the patterns found in the cluster analysis. The findings presented here contribute to the palynomorphological information on the genus Hypericum, which is crucial for taxonomy. Furthermore, pollen morphology, particularly aperture types, has proven to be a helpful diagnostic trait in the Hypericum genus.
Keywords: Hypericaceae; Hypericum; pollen morphology; UPGMA; Turkey